Economic and Financial Aspects of Operating Condo Hotels: A Qualitative Research In Poland - Krzysztof SALA (Communications of International Proceedings, 2024)
The aim of the article is to identify the key economic and financial aspects of condo hotels. The paper considers the Polish condo hotel market. Three main research methods used in the work are the following: criticism of literature, analysis of existing data and direct interview technique with managers of selected condo hotels in Poland. The results of the study indicate that in the long term, this type of investment involves a growing and difficult to fully assess uncertainty. This is due to the fact that the hotel market is particularly sensitive to unfavorable changes in the economic environment, economic downturn or unexpected fortuitous or pandemic events.  The passage of years and the gradual decapitalization of facilities are also among the factors that increase this uncertainty. The motivation to write the article resulted from the author's long-term personal scientific interests, related to the hotel industry and its aspects. The world literature lacks the latest studies on the economic and financial  aspects of condohotels, especially during  the war in Ukraine.
Keywords: Economy; hotel industry; investors; customers; tourism market; profits